Tanggung Jawab Dan Etika profesi Dokter Dalam Bidang Hukum - Mas'ud Idris (Universitas Negeri Gorontalo, 2009)
The increasing of public knowledge about raw and height of rights and obligations awarnes every cityzen makes health personel must take care when doing health service to public.health personel must take care applied,that later doesnt́ get demand from patient in the event of undesirable situation. medical conceived of a profession taht is a activity that gives service and containing two element namely:firstly,applies a knowledge set that sistematically structured to certain problems.second,problems has big relevance in the relationship with public fundamental values. kaa kunci:tanggung jawab,etika,profesi,dokter,hukum